Epidermal growth factor receptor (EGFR) density may not be the only determinant for the efficacy of EGFR‐targeted photoimmunotherapy in human head and neck cancer cell lines. Issue 5 (19th May 2018) - Peng, Wei; de Bruijn, Henriette S.; Farrell, Eric; Sioud, Mouldy; Mashayekhi, Vida; Oliveira, Sabrina; van Dam, Go M.; Roodenburg, Jan L. N.; Witjes, Max J. H.; Robinson, Dominic J.
Abstract : Objective: The aim of this study was to investigate the effects of targeted photoimmunotherapy (PIT) in vitro on cell lines with various expression levels of epidermal growth factor receptor (EGFR) using an anti‐EGFR targeted conjugate composed of Cetuximab and IR700DX, phthalocyanine dye. Materials and Methods: Relative EGFR density and cell binding assay was conducted in three human head & neck cancer cell lines (scc‐U2, scc‐U8, and OSC19) and one reference cell line A431. After incubation with the conjugate for 1 or 24 hours, cellular uptake and localization were investigated by confocal laser scanning microscopy and quantified by image analysis. Cell survival was determined using the MTS assay and alamarBlue assay after PIT with a 690 nm laser to a dose of 7 J.cm −2 (at 5 mW.cm −2 ). The mode of cell death was examined with flow cytometry using apoptosis/necrosis staining by Annexin V/propidium iodide, together with immunoblots of anti‐apoptotic Bcl‐2 family proteins Bcl‐2 and Bcl‐xL. Results: A431 cells had the highest EGFR density followed by OSC19, and then scc‐U2 and scc‐U8. The conjugates were localized both on the surface and in the cytosol of the cells after 1‐ and 24‐hour incubation. After 24‐hour incubation the granular pattern was more pronounced and in a similar pattern of a lysosomal probe, suggesting that the uptake of conjugates by cells was via receptor‐mediated endocytosis. The results obtained from the quantitative imaging analysis correlate with the level of EGFR expression. Targeted PIT killed scc‐U8 and A431 cells efficiently; while scc‐U2 and OSC19 were less sensitive to this treatment, despite having similar EGFR density, uptake and localization pattern. Scc‐U2 cells showed less apoptotic cell dealth than in A431 after 24‐hour targeted PIT. Immunoblots showed significantly higher expression of anti‐apoptotic Bcl‐2 and Bcl‐xL proteins in scc‐U2 cell lines compared to scc‐U8. Conclusion: Our study suggests that the effectiveness of EGFR targeted PIT is not only dependent upon EGFR density. Intrinsic biological properties of tumor cell lines also play a role in determining the efficacy of targeted PIT. We have shown that in scc‐U2 cells this difference may be caused by differences in the apoptopic pathway. Lasers Surg. Med. 50:513–522, 2018. © 2018 Wiley Periodicals, Inc.